2021
DOI: 10.1007/s10904-021-02116-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Crystal Structure, Electrical and Magnetic Properties of Spinel Mn-Cd Ferrite Nanoparticles

Abstract: Fe 2 Cd 1-x Mn x O 4 (x= 0, 0.25, 0.5, 0.75, 1) spinel ferrite nanoparticle samples were synthesized using a flash auto-combustion technique and analyzed using X-ray diffraction (XRD), scanning electron microscopy (SEM), and Fourier-transform infrared spectroscopy (FTIR). The inspection of dielectric and magnetic properties of the prepared ferrites was carried out by using broadband dielectric spectroscopy (BDS) and vibration sample magnetometer (VSM) measurements, respectively. Xray diffraction analysis verif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 52 publications
3
8
0
Order By: Relevance
“…The reported high values of corecivity in this work and its increase with Cd-content in samples with x > 0.0 could be referred to the presence of α-Fe 2 O 3 impurity phase in these samples. A similar behavior of the increase in coercivity with the increase in both Cd-content and α-Fe 2 O 3 has been reported [29]. According to Jahan et al [16], coercivity could be improved by unwanted magnetic construction, such as induced blocked particles, inside the nanoparticles' grains.…”
Section: Magnetic Analysissupporting
confidence: 71%
See 3 more Smart Citations
“…The reported high values of corecivity in this work and its increase with Cd-content in samples with x > 0.0 could be referred to the presence of α-Fe 2 O 3 impurity phase in these samples. A similar behavior of the increase in coercivity with the increase in both Cd-content and α-Fe 2 O 3 has been reported [29]. According to Jahan et al [16], coercivity could be improved by unwanted magnetic construction, such as induced blocked particles, inside the nanoparticles' grains.…”
Section: Magnetic Analysissupporting
confidence: 71%
“…Another aim is to study the effect of self-produced hematite phase on the coercivity of Cd-Zn nanoparticles. Whereas, reported coericivity values and their increase with both Cd-content and α-Fe 2 O 3 have been reported in Mn-Cd ferrites by the authors [29]. Future work will focus on further investigation of the role played by hematite phase in spinel ferrites. ]…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…The literature on Debye temperatures of spinel ferrites from the diffraction data is quite limited, and some of the published fits appear to be problematic. , The values obtained from diffraction are generally lower than those from IR or elastic constants, and this was postulated to be an artifact of using the Fd 3̅ m space group in structural refinements instead of the claimed true space group of F 4̅3 m . However, the average Debye temperatures found here are significantly higher than those previously determined from diffraction and in quite good agreement with those reported from IR, 569 K for ZnFe 2 O 4 , and elastic constants, which generally lie in the 450–700 K range for spinel ferrites. , This, in conjunction with our analysis establishing Fd 3̅ m as the true space and the poor agreement between the diffraction data and the model reported by Modi et al and Lakhani et al, points to the previous values reported from diffraction being inaccurate due to insufficient data quality or potentially varying defect structures.…”
Section: Resultssupporting
confidence: 50%